Beyond immune suppression: the intrinsic function of PD-L1 in ovarian cancer and melanoma - Zhu, Hengrui; Zhang, Rugang (Translational Cancer Research, 2017)
Accumulating evidences have revealed that the immune response in cancer microenvironment plays important roles in tumor progression and treatment. Tumor infiltrating immune cells include effector T cells subsets (1), regulatory T cells (Tregs) (2), antigen presenting cells (APCs) (3) and myeloid-derived suppressor cells (MDSCs) (4). The interaction between tumor cells and these immune cells regulates tumor dissemination, relapse and metastasis (5). Tumor cells have developed multiple different mechanisms to evade host immune surveillance, including programmed cell death 1 ligand (PD-L1, B7-H1, CD274) and programmed cell death receptor 1 (PD-1, CD279) pathway, also known as PD pathway. PD-L1 is a functional ligand of PD1 on effector T cells, upon engagement, the PD pathway can inhibit the function of effector T cells, affect the survival and proliferation of activated T cells and lead to T cells exhaustion (6,7). PD-L1 is seldom expressed on normal human tissues, however, PD-L1 protein is found to be overexpressed in many human cancers. The interaction of PD-L1 on tumor cells with PD1 suppresses T cells function and help tumor cells to escape anti-tumor immune response (8,9).